GENETIC STRUCTURALISM AND VALUE OF CHARACTER EDUCATION IN THE MONOLOGUE MATINYA TOEKANG KRITIK, THE DEATH OF CRITICIZERS BY AGUS NOOR - Oktalifa Hanna Maulina; Suyitno Suyitno; Nugraheni Eko Wardani (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2018)
The aims of this research are to describe writer’s point of view of Agus Noor on monologue Matinya Toekang Kritik, the Death of Criticisers, text structure, social structure, and tolerance attitude as the character building values in the work. This research is the descriptive qualitative research. Data were validated using theory triangulation and data triangulation. The data were analyzed using interactive analysis techniques and content analysis.  The results are: (1) Drama writer group’s point of view is social humanism, (2) Monolog text structure describes demonstrative life with Javanese values that found through structuralism analysis approach, (3) Monologue text structure is divided into harmony, honourability, the lifestyle of priyayi and wong cilik  and also the relationship between priyayi  and government, and (4) The most dominant character building is tolerance shown explicitly or implicitly by the players.